2011
DOI: 10.3354/meps09114
|View full text |Cite
|
Sign up to set email alerts
|

Dietary metal and macro-nutrient intakes of juvenile lemon sharks determined from the nutritional composition of prey items

Abstract: The trace element requirements of sharks are poorly understood and the dietary intake of metals from prey items in wild sharks has not been measured. In this study whole prey of nursery bound juvenile lemon sharks Negaprion brevirostris, from Bimini, Bahamas were analysed for carcass total protein, lipids, carbohydrates, ash content, energy, and elemental composition. Metal analysis included 415 prey items from 18 species (fish: Atherinidae, Belonidae, Gerreidae, Haemulidae, Lutjanidae, Scaridae, Sphyraenidae;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…This difference converts to 232.591 kJ day -1 (Jobling, 1995). Given that yellow fin mojarra (Gerres cinereus), the primary prey of juvenile lemon sharks in Bimini have an average mass of 41.38 g and energy density of 15.58 kJ g -1 (Pettitt-Wade et al, 2011), this 232.591 kJ difference represents 0.96 mojarras, or a 25% increase in the expected daily energetic requirement of a shark. With such clear improvements over other modelling techniques, we strongly recommend the covariate-corrected modelling approach for establishing ṀO2 predictive equations across different body sizes.…”
Section: Discussionmentioning
confidence: 99%
“…This difference converts to 232.591 kJ day -1 (Jobling, 1995). Given that yellow fin mojarra (Gerres cinereus), the primary prey of juvenile lemon sharks in Bimini have an average mass of 41.38 g and energy density of 15.58 kJ g -1 (Pettitt-Wade et al, 2011), this 232.591 kJ difference represents 0.96 mojarras, or a 25% increase in the expected daily energetic requirement of a shark. With such clear improvements over other modelling techniques, we strongly recommend the covariate-corrected modelling approach for establishing ṀO2 predictive equations across different body sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Average gross energy density was 13.79± 0.87 kJ g −1 (wet mass), similar to the energy density of demersal western Atlantic reef fish that lionfish would prey upon (Schwartzkopf and Cowan, 2017;Welicky et al, 2018). Pettitt-Wade et al (2011) found no difference in the energy density of small forage fish including A. stipes between seasons in The Bahamas, so this energy density was used for all treatments and experiments.…”
Section: Prey Calorimetrymentioning
confidence: 64%